Progenitors in the adult cerebral cortex: Cell cycle properties and regulation by physiological stimuli and injury - Simon, Christiane; Götz, Magdalena; Dimou, Leda (Glia, 2011)
The adult brain parenchyma contains a widespread population of progenitors generating different cells of the oligodendrocyte lineage such as NG2+ cells and some mature oligodendrocytes. However, it is still largely unknown how proliferation and lineage decisions of these progenitors are regulated. Here, we first characterized the cell cycle length, proliferative fraction, and progeny of dividing cells in the adult cerebral cortex and then compared these proliferation characteristics after two distinct stimuli, invasive acute brain injury and increased physiological activity by voluntary physical exercise. Our data show that adult parenchymal progenitors have a very long cell cycle due to an extended G1 phase, many of them can divide at least twice and only a limited proportion of the progeny differentiates into mature oligodendrocytes. After stab wound injury, however, many of these progenitors re‐enter the cell cycle very fast, suggesting that the normally long G1 phase is subject to regulation and can be abruptly shortened. In striking contrast, voluntary physical exercise shows the opposite effect with increased exit of the cell cycle followed by an enhanced and fast differentiation into mature oligodendrocytes. Taken together, our data demonstrate that the endogenous population of adult brain parenchymal progenitors is subject to profound modulation by environmental stimuli in both directions, either faster proliferation or faster differentiation. © 2011 Wiley‐Liss, Inc.